2013
DOI: 10.3997/1873-0604.2013070
|View full text |Cite
|
Sign up to set email alerts
|

Case studies of incorporation of prior information in electrical resistivity tomography: comparison of different approaches

Abstract: Many geophysical inverse problems are ill-posed and their solution non-unique. It is thus important to reduce the amount of mathematical solutions to more geologically plausible models by regularizing the inverse problem and incorporating all available prior information in the inversion process. We compare three different ways to incorporate prior information for electrical resistivity tomography (ERT): using a simple reference model or adding structural constraints to Occam's inversion and using geostatistica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 44 publications
(91 reference statements)
0
42
0
Order By: Relevance
“…The generalized range can be subsequently used to compute the value of the covariance (equation 1) for any combination of model parameters in the grid and build the parameter covariance matrix used during the inversion process. Applications for static conditions (Linde et al, 2006;Hermans et al, 2012;Caterina et al, 2014) have shown that the use of a CCI has generally led to a strong improvement of the resulting image compared with SCI. This operator also smooths the distribution of model parameters through the covariance matrix, but to a level that can be controlled by the correlation length.…”
Section: Model Parameter Covariance Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…The generalized range can be subsequently used to compute the value of the covariance (equation 1) for any combination of model parameters in the grid and build the parameter covariance matrix used during the inversion process. Applications for static conditions (Linde et al, 2006;Hermans et al, 2012;Caterina et al, 2014) have shown that the use of a CCI has generally led to a strong improvement of the resulting image compared with SCI. This operator also smooths the distribution of model parameters through the covariance matrix, but to a level that can be controlled by the correlation length.…”
Section: Model Parameter Covariance Matrixmentioning
confidence: 99%
“…However, such a constraint is often not coherent with the geology. Thus, many alternatives have been developed in static imaging, such as blocky inversion (Farquharson and Oldenburg, 1998), structural inversion (Kaipio et al, 1999;Doetsch et al, 2012a), minimum support (MS) and gradient support functionals (Portnaguine and Zhdanov, 1999;Blaschek et al, 2008), or other prior information incorporation methods (Caterina et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Borehole EM data could also be used as prior information to further improve the 571 ERT inversion (e.g. Caterina et al, 2014). 572…”
Section: Discussion 529mentioning
confidence: 99%
“…New constraints have been developed including blocky inversion [77], minimum gradient support [78], structural inversion [79], geostatistical inversion [44] or guiding images [80]. These constraints have proved to be efficient in many field cases (e.g., [81]). …”
Section: Time-lapse Ertmentioning
confidence: 99%